Bounds for the Periods of Periodic Solutions of Ordinary Differential Equations - Ignat'ev, A. O. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We consider a nonautonomous system of ordinary differential equations. It is supposed that this system has a periodic solution. We establish the lower bound for the period of this solution.